2011
DOI: 10.4236/ijcm.2011.21008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor with PGE2 after One Previous Cesarean Section: 18 Years Experience in a University Hospital

Abstract: Objective: To review the outcome of prostaglandin induction of labor in term pregnant women with previous one ce-sarean section compared to those without previous Cesarean section. Design: 18 years retrospective review of hospital records and case note review of index cases. Setting: University hospital. Population: Three hundred and twenty two women who had their labor induced with prostaglandin E2. One hundred and sixty one women had one previous Ce-sarean section. Methods: This study was conducted at King F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Doshi et al [11] and others [1213] reported the interesting finding that maternal age >35 years and fetal weight >3.5 kg were associated with decreased chances of successful TOLAC. In the present study, the mean age was 25.81±2.72 years, which is younger that reported in literature from the western world [8] but comparable with that reported in studies of Asian countries [910]. This may be due to nutritional, financial, or ethnical factors that vary among these regions.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Doshi et al [11] and others [1213] reported the interesting finding that maternal age >35 years and fetal weight >3.5 kg were associated with decreased chances of successful TOLAC. In the present study, the mean age was 25.81±2.72 years, which is younger that reported in literature from the western world [8] but comparable with that reported in studies of Asian countries [910]. This may be due to nutritional, financial, or ethnical factors that vary among these regions.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, the reported rate was 64.34%. The rate of successful VBAC in patients with spontaneous onset of labour pains is reported from 67.2% [9] to 72.3% [10]; in present study it was 86.82%.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A comparable study by Alsayegh AK et al, Jitesh S et al, Qahtani NA et al, Monohar R et al, shows similar results. 5,6,9,11,12 We have included patients with gestational age >37 weeks up to 42 weeks, period of gestation. Most of cases were 37-39 weeks 79 (52.7%) and 71 (47.3%).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that increased uptake of planned VBAC could decrease the overall cesarean section rate by around 5%. 5 In a 2010 consensus conference, the National institutes of Health (NIH) examined the safety and outcome of trial of labor after cesarean (TOLAC) and VBAC and factors associated with decreasing rates. The NIH panel had recognized that TOLAC was a reasonable option for many women who had prior cesarean delivery and called all organizations to facilitate access to TOLAC.…”
Section: Introductionmentioning
confidence: 99%